Tax audit: problems faced by a tax agent and the Inland Revenue Board of Malaysia (IRBM) on the settlement of corporate tax liabilities / Sheka Suhada Mustapha - Mustapha, Sheka Suhada (2014)
Most businesses fear the words “tax audit” as they are often associated with additional taxes and hefty penalties. Tax audits also tend use up a lot of resources of taxpayers such as additional costs involved in engaging tax professionals who is the tax agent as well as the reallocation of resources for the purpose of gathering information needed and liaising with the tax authorities. The best way to understand the tax audit is to gain knowledge about tax followed by the guidelines and framework by Inland Revenue Board of Malaysia (IRBM). The emphasis in the research is to provide ways for the taxpayers from audited by the Inland Revenue Board of Malaysia (IRBM) and alternatives for the tax agent to consult and advice the taxpayers about the tax audit. Therefore, tax audit cases that had been audited by Inland Revenue Board of Malaysia (IRBM) are discussed in this research. However, the tax audit cases can explained the exactly problems between tax agent and Inland Revenue Board of Malaysia in settling the corporate tax whilst the tax agent already done the tax compliance and audit according the laws and regulations. This research provides information on the types of tax audit typically conducted by the Inland Revenue Board of Malaysia (IRBM), the audit process, the penalties involved as well. Furthermore, the research indicates as well the pre-field audit by the team of tax agent to prevent the client from being audited. The aim of this study (i) to find out whether there is a problem with tax audit between the tax agent in question and the Inland Revenue Board of Malaysia (IRBM) on corporate tax liabilities, (ii) to find out the common problems detected in tax audit by the tax agent and the Inland Revenue Board of Malaysia (IRBM), (iii) to determine whether the clients of the tax agent are able to provide full evidence for tax audit as requested by both the tax agent and the Inland Revenue Board of Malaysia (IRBM),(iv) to analyze the procedures of detecting problems during tax audit by the tax agent and the Inland Revenue Board of Malaysia (IRBM). The data cover by the interview statement, document search and tax audit cases handled by the experience of tax department if the said tax agent. The study showed that the tax manager and tax supervisor had give their responses through interviews and document search based on the tax audit cases of the said tax agent. The aim of this is to fulfil the requirements of the research objectives.